X-Ray Polarization of the Magnetar 1E 1841−045 - Rachael Stewart; George A. Younes; Alice K. Harding; Zorawar Wadiasingh; Matthew G. Baring; Michela Negro; Tod E. Strohmayer; Wynn C. G. Ho; Mason Ng; Zaven Arzoumanian; Hoa Dinh Thi; Niccolò Di Lalla; et al. (The Astrophysical Journal Letters)
We report on IXPE and NuSTAR observations beginning 40 days after the 2024 outburst onset of magnetar 1E 1841−045, marking the first IXPE observation of a magnetar in an enhanced state. Our spectropolarimetric analysis indicates that both a blackbody (BB) plus double power-law (PL) and a double blackbody plus power-law spectral model fit the phase-averaged intensity data well, with a hard PL tail (Γ = 1.19 and 1.35, respectively) dominating above ≈5 keV. For the former model, we find the soft PL (the dominant component at soft energies) exhibits a polarization degree (PD) of ≈30% while the hard PL displays a PD of ≈40%. Similarly, the cool BB of the 2BB+PL model possesses a PD of ≈15% and a hard PL PD of ≈57%. For both models, each component has a polarization angle (PA) compatible with celestial north. Model-independent polarization analysis supports these results, wherein the PD increases from ≈15% to ≈70% in the 2–3 keV and 6–8 keV ranges, respectively, while the PA remains nearly constant. We find marginal evidence for phase-dependent variability of the polarization properties, namely a higher PD at phases coinciding with the hard X-ray pulse peak. We compare the hard X-ray PL to the expectation from resonant inverse Compton scattering (RICS) and secondary pair cascade synchrotron radiation from primary high-energy RICS photons; both present reasonable spectropolarimetric agreement with the data, albeit the latter does so more naturally. We suggest that the soft PL X-ray component may originate from a Comptonized corona in the inner magnetosphere.